Serum levels of glial fibrillary acidic protein and Nogo-A in children with autism spectrum disorders - Cetin, Ihsan; Tezdig, Ihsan; TARAKCIOGLU, Mahmut Cem; Kadak, Muhammed Tayyib; Demirel, Omer Faruk; Ozer, Omer Faruk; ÖZER, ÖMER FARUK (My University, 2016)
Context: Improved biomarkers would facilitate the diagnosis and treatment of autism spectrum disorders (ASD).